Lucky ducklings - Moore, Eva.; Carpenter, Nancy (New York : Orchard Books, 2013)
While following their mother through town, five little ducklings fall into a storm drain.
"A true rescue story"--Cover.
This rescue happened in June of 2000 in the town of Montauk, New York, on the end of Long Island. The people who helped the lucky ducks are Joe Lenahan, Paul Greenwood, Dennis Sisco, and Perry Aaland.
Keywords: Ducks -- Fiction; Animals -- Infancy -- Fiction; Rescues -- Fiction; Ducks -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Rescues -- Juvenile fiction; Picture books for children